Direct ageing experiments on nanometre-scale aluminium alloy samples. (1st June 2022) - Banhart, J.; Chen, Y.-S.; Guo, Q.N.; Marceau, R.K.W.; Cairney, J.M.
Abstract: Studies of the kinetics of precipitation in aluminium alloys help to understand the role of quenched-in excess vacancies in the ageing process. Investigations of ageing in nanometre-sized samples are valuable because excess vacancies are believed to anneal out quickly while the alloy is still supersaturated with solute atoms. We prepare samples suitable for atom probe tomography (APT) with a sharp tip of some tens of nm radius and verify that they can be solutionised and quenched, after which they are still suitable for APT. The investigated Al-Zn alloy is known to show extremely strong clustering after quenching of the bulk material but we find that this clustering is completely suppressed in solutionised and quenched samples. Precipitation calculations explain this by a fast loss of vacancies, within seconds, during and after quenching. As such calculations also suggest that at elevated temperatures clustering could occur in the thermal equilibrium, we carry out exploratory ageing experiments on APT samples at 100°C and 135°C. No clusters are found in such samples, which could be related to experimental restrictions (Zn losses) or unfavourable nucleation conditions in nm-sized samples. Graphical abstract: Image, graphical abstract